miR-223 Inhibits the Polarization and Recruitment of Macrophages via NLRP3/IL-1β Pathway to Meliorate Neuropathic Pain - Junsong Zhu; Jinmei Yang; Jianguo Xu (Pain Research and Management)
Background. miRNA is an essential factor in neuropathic pain. However, the underlying mechanism of miRNA in neuropathic pain remains unclear. Objective. To explore the potential role of miR-223 in neuropathic pain in a mice model of chronic sciatic nerve injury. Methods. Mice were divided into the sham group, CCI group, CCI + Lenti-vector group, and CCI + Lenti-miR-223 group. Flow cytometry was used to detect the neuronal apoptosis and the proportion of M1/M2 macrophages in each group. Western blot was used to detect the protein expression levels of ASC, caspase-1, IL-1β, and IL-18 in each group. Luciferase activity assay detects the binding of miR-223 and NLRP3. Macrophage chemotaxis experiments verified the anti-inflammatory effect of miR-223 in vitro. Results. The overexpression of miR-233 significantly reduced the neuropathic pain caused by CCI and reduced the apoptosis and inflammatory factor expression. miR-223 inhibits the expression of NLRP3 by directly binding to the 3′-untranslated region. Overexpression of miR-223 reduces the protein levels of NLRP3, ASC, caspase-1, IL-1β, and IL-18 in the spinal cord of CCI mice, increases the proportion of M2-type macrophages, and reduces the proportion of M1-type macrophages. Conclusion. miR-223 may facilitate the development of neuropathic pain in CCI mice by inhibiting NLRP3-mediated neuroinflammation.